PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR GEOGRAFI - Saiful Amin (JPG (Jurnal Pendidikan Geografi), 2017)
This research aimed to examine the effect of Problem Based Learning (PBL) model on the critical thinking skill and student learning outcome. The research was conducted in the 11th grade of Social Science, Public Senior High School (SMAN 6 Malang). The research material was the problems of demography. Research method was quasi experiment with non equivalent control group design. Data analysis used t-test technique (independent sample t-test). The research result showed that PBL learning model affected on the critical thinking skill and geography student learning outcome in SMAN 6 Malang. The average gain score of experimental class was higher, which is 33.10 than control class, which is 16.24. Computation result of data t-test analysis to the PBL learning model was obtained p-level which smaller than 0.05 (p<0.05) with significance 2 tailed 0.000. Keywords: PBL, critical thinking skill, geography learning outcome